An improved plant treatment agent - Ahmed, Osumanu Haruna; Omar, Latifa; Ab. Majid, Nik Muhamad (2011)
The present invention provides a slow release granule composition for the delivery of one or more plant treatment agents. The composition comprises an organic solution consisting peat soil liquid obtained from a peat material and urea. The granule composition is useful for the controlled delivery of fertilizers and nutrients to plants and as a soil amendment. also disclosed is a method of treating a plant with a plant treatment agent, comprising applying a slow release granule composition of the present invention and a method to prepare the slow release granule composition.